The Management of Reading Park Case study in Kaba Kamboja Batipuh Panjang - Fitri Anggeli; Solfema Solfema (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2021)
Reading park it means of a place to increase children’s interest in reading which makes reading a daily culture in improving the quality of human resources. In Kaba Kamboja, the withdrawal of interest in reading is carried out by managers the managers is who are collage students. The manager himself which has several strategies in its services, especially learning management in the form of : 1) critical awareness 2) motivating children, 3) two-way communication, 4) monitoring activities, and 5) program providers as needed. In the case of kaba kamboja its focuses on reading interest to make area on Batipuh Panjang are reading culture. The purpose of managing the reading park itself now more focused on children’s reading culture. Kaba Kamboja is opened every times a week and more towards tutoring and becoming a focus for playing and learning areas for the children of the jambak village